PENGARUH TINGKAT PERPUTARAN MODAL KERJA, UKURAN PERUSAHAAN DAN TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS PERIODE 2016-2018 PADA LPD DI DENPASAR - Kadek Prayogy Martika Diartiwi; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2021)
Rural communities are the focus of national development to support economic development in rural areas, by conducting credit and financing activities. Economic growth can be increased by increasing the financial sector. To support the economic development of rural communities, the Provincial Government of Bali developed the LPD, which is a non-bank financial institution regulated in Regional Regulation No. 3 of 2017 Bali Province. Research locations of all LPDs in Denpasar amounted to 35x 3 years of research. Saturated sampling is a sampling technique used in this study. Data collection is done by non-participant observation methods. And the data analysis technique used is multiple linear regression analysis and the classic assumption test consisting of: normality test, heteroscedasticity test, autocorrelation test, multicollinearity test. Based on the results of the study concluded (1) The variable level of working capital turnover has a negative effect on profitability. (2) Company size variable does not affect profitability. (3) The variable growth rate of the company has no effect on profitability. From the results of regression analysis, it shows that partially the working capital turnover has a significant negative effect on profitability. This is due to the shorter time period in lending policies making capital turnover faster. The size of the company is not a guarantee that the company has the ability to generate good profits. This insignificant effect is caused by the larger size of a company, then the company will need greater costs to carry out operational activities. This insignificant effect is caused by the higher growth of a company, it will not be able to reduce the company's profitability.